\(\frac{x}{3.5}+\frac{x}{5.7}+\frac{x}{7.9}+...+\frac{x}{13.15}=\frac{4}{45}\)
\(\Leftrightarrow\frac{x}{2}.\left(\frac{2}{3.5}+\frac{2}{5.7}+\frac{2}{7.9}+...+\frac{2}{13.15}\right)=\frac{4}{45}\)
\(\Leftrightarrow\frac{x}{2}.\left(\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+...+\frac{1}{13}-\frac{1}{15}\right)=\frac{4}{45}\)
\(\Leftrightarrow\frac{x}{2}.\left(\frac{1}{3}-\frac{1}{15}\right)=\frac{4}{45}\)
\(\Leftrightarrow\frac{x}{2}.\frac{4}{15}=\frac{4}{45}\)
\(\Leftrightarrow\frac{x}{2}=\frac{4}{45}:\frac{4}{15}\)
\(\Leftrightarrow\frac{x}{2}=\frac{1}{3}\)
\(\Leftrightarrow x=\frac{1}{3}.2\)
\(\Leftrightarrow x=\frac{2}{3}\)
Vậy x = \(\frac{2}{3}\)
_Chúc bạn học tốt_